Effect of Public Deliberation on Attitudes toward Return of Secondary Results in Genomic Sequencing. Issue 1 (16th June 2016) - Gornick, Michele C.; Scherer, Aaron M.; Sutton, Erica J.; Ryan, Kerry A.; Exe, Nicole L.; Li, Ming; Uhlmann, Wendy R.; Kim, Scott Y.H.; Roberts, J. Scott; De Vries, Raymond G.
Abstract: The increased use of genomic sequencing in clinical diagnostics and therapeutics makes imperative the development of guidelines and policies about how to handle secondary findings. For reasons both practical and ethical, the creation of these guidelines must take into consideration the informed opinions of the lay public. As part of a larger Clinical Sequencing Exploratory Research (CSER) consortium project, we organized a deliberative democracy (DD) session that engaged 66 participants in dialogue about the benefits and risks associated with the return of secondary findings from clinical genomic sequencing. Participants were educated about the scientific and ethical aspects of the disclosure of secondary findings by experts in medical genetics and bioethics, and then engaged in facilitated discussion of policy options for the disclosure of three types of secondary findings: 1) medically actionable results; 2) adult onset disorders found in children; and 3) carrier status. Participants' opinions were collected via surveys administered one month before, immediately following, and one month after the DD session. Post DD session, participants were significantly more willing to support policies that do not allow access to secondary findings related to adult onset conditions in children ( Χ 2 (2, N = 62) = 13.300, p = 0.001) or carrier status ( Χ 2 (2, N = 60) = 11.375, p = 0.003). After one month, the level of support for the policy denying access to secondary findings regarding adult‐onset conditions remained significantly higher than the pre‐DD level, although less than immediately post‐DD ( Χ 2 (1, N = 60) = 2.465, p = 0.041). Our findings suggest that education and deliberation enhance public appreciation of the scientific and ethical complexities of genome sequencing.